People with dementia can learn compensatory movement maneuvers for the sit-to-stand task: a randomized controlled trial - Werner, Christian; Wiloth, Stefanie; Lemke, Nele; Oster, Peter; Bauer, Jürgen M.; Hauer, Klaus (Journal of Alzheimer's disease, 2017)
Background: A complex motor skill highly relevant to mobility in everyday life (e.g., sit-to-stand [STS] transfer) has not yet been addressed in studies on motor learning in people with dementia (PwD). Objective: To determine whether a dementia-speci
Gesehen am 28.11.2018